Exploring the barriers and incentive architecture for modifying smoke exposures among asthmatics. (3rd July 2019) - Tower, Craig; Butz, Arlene; Lewis-Land, Cassia; Zhu, Meng; Jassal, Mandeep S.
Abstract: Background : The socio-structural barriers for reducing secondhand smoke exposure (SHSe) among children with asthma may be insurmountable for low-income caregivers. Health promoting financial incentives (HPFIs) are increasingly being used in the adult population to motivate and sustain tobacco-reduction behaviors. We assessed barriers to SHSe reduction and means to overcome them through the design of an HPFI-based, caregiver-targeted SHSe reduction study. Methods : Using a mixed-methods design, we conducted semi-structured in-depth interviews among low-income primary caregivers of children with asthma residing in Baltimore City. Quantitative data using an online survey were used to augment interview findings. Results : Home smoking restrictions were a frequently referenced strategy for decreasing SHSe, but interviewees ( n = 22) described the complex social pressures that undermine reduction efforts. Caregivers redirected conversations from broadly implemented smoking bans towards targeted reduction strategies among mothers and members of their social network who are active smokers. Participants converged on the notion that sustainable SHSe reduction strategies are realizable only for mothers who are active smokers, possess high self-efficacy and social structures that promote cessation. Survey data ( n = 56) clarified the multiple contexts that underlie pediatric SHSe and preferred HPFI architecture that included fixed, recurrent payments contingent on reduced nicotine biomarkers and completion of basic asthma education classes. Conclusions : Based on the combined analyses, we envision testing a HPFI-based study design whose optimal target population included low-income caregivers and members of their social network where incentives are tied to pediatric biomarkers and asthma education—an integrated approach that has not yet been used in pediatric tobacco studies.